1996
DOI: 10.1210/endo.137.2.8593799
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain production by cultured adrenal cells.

Abstract: The adrenal cortex releases a sodium pump inhibitor. The present studies tested whether this material was endogenous and identical to ouabain by 1) studying the production of ouabain in long term cultures of adrenocortical cells, 2) seeking evidence that ouabain might be taken up from exogenous sources by adrenocortical cells, 3) examining the release of adrenocortical cells loaded with exogenous ouabain, 4) attempting to stimulate ouabain steroidogenesis in cultured adrenocortical cells, and 5) performing fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was suggested that Ouabain is a hormone when Hamlyn and Mathews demonstrated the presence in plasma of a substance similar to ouabain in plants [22,37]. Thereafter, it was shown that endogenous ouabain is synthesized and secreted by the hypothalamus [38,39] and the adrenocortical gland [40,41,42]. The status of ouabain as a hormone was strengthened upon the discovery of increased concentrations in plasma during exercise, ingesting salty foods, and in pathological conditions such as arterial hypertension and myocardial infarction [43,44,45,46,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that Ouabain is a hormone when Hamlyn and Mathews demonstrated the presence in plasma of a substance similar to ouabain in plants [22,37]. Thereafter, it was shown that endogenous ouabain is synthesized and secreted by the hypothalamus [38,39] and the adrenocortical gland [40,41,42]. The status of ouabain as a hormone was strengthened upon the discovery of increased concentrations in plasma during exercise, ingesting salty foods, and in pathological conditions such as arterial hypertension and myocardial infarction [43,44,45,46,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…The Cardiotonic Steroids (CTS) constitute a family of steroid hormones which decades ago were discovered in plants e.g., Ouabain from an African tree (Acokanthera ouabaio). It is nowadays established that Ouabain is synthesized and released mainly in the adrenal gland as demonstrated in different species [ 22 24 ]. Moreover it was shown that, like other “stress hormones”, they are part of the Hypothalamic–Pituitary–Adrenal axis and stimulated by the adrenocorticotropic hormone (ACTH) and Angiotensin II [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the clinical preparations include digitoxin, digoxin, lantoside C and strophanthin K. Endogenous CTS are endogenous digitalis-like factors (EDLF) found in mammalian tissues and body fluids (including the brain, adrenal gland, plasma, urine, and placenta, etc. ), such as ouabain-like substances found in human plasma and adrenal glands, digitalis-like substances found in human urine and placenta, ouabain-like substances extracted from bovine hypothalamus (Goto et al, 1990;Hamlyn et al, 1991;Tymiak et al, 1993;Doris et al, 1996;Ma et al, 2012). Whether they are endogenous or exogenous, the basic structure of CTS determines that they have similar effects, and different modification groups provide them with rich pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%